PEMANFAATANE-LEARNING DALAMPEMBELAJARAN BAHASA INDONESIA - Setyawan Pujiono (Jurnal Cakrawala Pendidikan, 2008)
The Indonesian language teachingand learning is essentially focused on theability to use the four major language skills (writing, reading, speaking andlistening) in real life.An attempt to improve the skills can be made by changing theclassical teaching model into a modernand creative one. Such a change does notmean eliminating the existing teachingand learning models, but trying to developand combine them with a modern one. Therefore, an e-Iearning-based basedteachingand learning method needs to be implemented in the Indonesian languageteachingand learning process.. The use of e-Iearning in this process will·overcomesome problems related to time, distance,materials,. and costs which have been theproblems for teachers and· students. The useof this method .is expected to givecomplete·and various information and materials through internet downloading.Besides, other benefits, such as flexible. timeand space during the process, willresult in students' independence and creativity.